Electronic institutions for B2B: dynamic normative environments - Henrique Lopes Cardoso (2008)
The regulation of the activity of multiple autonomous entities represented in a multi-agent system, in environments with no central design (and thus with no cooperative assumption), is gaining much attention in the research community. Approaches to this concern include the use of norms in so-called normative multi-agent systems and the development of electronic institution frameworks. In this paper we describe our approach towards the development of an electronic institution providing an enforceable normative environment. Within this environment, institutional services are provided that assist agents in forming cooperative structures whose commitments are made explicit through contracts. Our normative framework borrows some concepts from contract law theory. Contracts are formalized using norms which are used by the institution while monitoring agents' activities, thus making our normative environment dynamic. We regard the electronic institution as a means to facilitate both the creation and the enforcement of contracts between agents. A model of "institutional reality" is presented that allows for monitoring the fulfillment of norms. The paper also distinguishes our approach from other developments of the electronic institution concept. We address the application of our proposal in the B2B field, namely regarding the formation of Virtual Organizations.